Latent and Eggs Production of Banggai Cardinal (Pterapogon kauderni, Koumans 1933) on Various Salinity Levels: Conservation Efforts - Pietoyo, Atiek; Andayani, Sri; Suprijanto, Agoes (The Journal of Experimental Life Science, 2016)
The aim of this study is to determine the best salinity level on latent and eggs production of Banggai Cardinal (Pterapogon kauderni Koumans 1993) based on first brood and brood production of Banggai Cardinal in the treatment. Water quality measurement was carried out every day to maintain water quality. Water quality measurement showed suitable salinity for Banggai Cardinal breeding. Brood latent showed no significant difference between the treatments. Total of 27 ppt is the level of salinity for Banggai Cardinal reproduction to gain positive respond on eggs production (42.3333 ± 7 eggs). Keywords: Banggai Cardinal, Eggs Production, Latent, Salinity.